Benefits of Hip Hop Dance for obese children and adolescents: A systematic review - Taise Tomio; Janaina Niehues; Ana Souza; Wanessa Zanotto; Camila Adam; Samuel Fragnani; Tatyana Nery; Ana Gonzales; Robson Lemos; Patrícia Haas (Revista Brasileira de Atividade Física e Saúde)
Introduction: The infant juvenile obesity is currently one of the most serious public health problems of the 21st century, being directly related to physical inactivity as a decisive factor in the worldwide epidemic. The programs of conventional workouts have become not so attractive for this particular population.  Because of that the access and permanence in those structured physical activity programs for obese adolescents are difficult. This systematic review has the general goal to verify what benefits the systematic practice of hip hop dance, can promote in obese children and adolescents. Methods: The search for relevant articles was conducted in the electronic databases Medline (Pubmed), Cochrane, LILACS, SciELO from January through June 2014, being structured as [(hip hop /) and (obesity /) and (children/ adolescent), controlled and randomized trials were included regarding the systematic practice of hip hop dance as exercise and its benefits for obese children and adolescents, subjects aged 2-19, considered obese and/or overweight. Results: A total of 21 articles were identified in the survey.  Based on the found eligible articles for the full review, only one article met all the inclusion criteria. Conclusions: This preliminary study is intended to broaden the context in health for adolescents and children suffering from overweight and/or obesity, recommending an intervention through dance hip hop, it would be an important modality association for possible monitoring and reducing the risk of associated comorbidities. In this field of research, there is a lack of studies of high methodological quality, which may be able to demonstrate the benefits of this type of intervention.